2005
DOI: 10.1530/rep.1.00723
|View full text |Cite
|
Sign up to set email alerts
|

Cytotrophoblast differentiation in the first trimester of pregnancy: evidence for separate progenitors of extravillous trophoblasts and syncytiotrophoblast

Abstract: It is commonly accepted that a single pool of villous cytotrophoblasts are precursors of both syncytiotrophoblast and extravillous trophoblasts during the first trimester. Here we present evidence that these two trophoblast subpopulations arise from separate progenitors that have different survival characteristics when studied in villous explant cultures. Dual staining with chloromethylfluorescin diacetate and ethidium bromide revealed degeneration of the syncytiotrophoblast by non-apoptotic mechanisms within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 29 publications
7
45
0
Order By: Relevance
“…However, like primary EVTs, the villous explant tissue itself has a limited period of viability in culture, meaning that outgrowth expansion can only be tracked for a few days. 31 …”
Section: Explant Culture Modelsmentioning
confidence: 99%
“…However, like primary EVTs, the villous explant tissue itself has a limited period of viability in culture, meaning that outgrowth expansion can only be tracked for a few days. 31 …”
Section: Explant Culture Modelsmentioning
confidence: 99%
“…However, when cultured, isolated villous cytotrophoblasts (even from early gestation placentae) differentiate to form the multinucleated syncytiotrophoblast (Dodeur et al 1990). Furthermore, work by ourselves and others has suggested that rather than existing as one homogenous bipotent population, cytotrophoblast subpopulations are primed to differentiate into either syncytiotrophoblast or extravillous trophoblast (Aboagye-Mathiesen et al 1996, James et al 2005, Telugu et al 2013. Indeed, many epithelial stem cell populations have the ability to generate committed progenitors, referred to as transit amplifying cells, which are able to expand the progenitor pool in tissues with rapid growth or high turnover (Blanpain et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These trophoblast cells interact with the uterus and produce functional factors to modify maternal physiological systems, and render enough blood flow and nutrients to the fetal-maternal interface (Burrows et al 1996, Lyall et al 1999, Watson & Cross 2005, Osol & Mandala 2009). In the villous tips which contact the maternal decidua, the cytotrophoblast (CTB) progenitor cells can develop and break the syncytiotrophoblast (STB) layer, assemble as the extravillous trophoblast column (TC), and further invade into the decidua to form EVTs (James et al 2005). The proximal portion of TC maintains their proliferative abilities, while trophoblast cells from the distal part invade into the decidua and even deeper into the myometrium, in order to achieve appropriate remodeling of maternal spiral artery and better anchor the fetus to the uterus (Osol & Mandala 2009).…”
Section: Introductionmentioning
confidence: 99%